Evaluation of the competency-based medical education curriculum - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Apollo Medicine)
Competency-based medical education (CBME) is an approach to producing competent doctors by the adoption of a framework of competencies, which in turn are derived from the needs of the patients and the general population. A number of expected outcomes have been identified for different stakeholders and efforts should be taken to accomplish them. Evaluation is an important aspect of any initiative and the same stands true even in the case of CBME as it has been introduced across all the medical colleges in the nation and the future of thousands of students depend on the same. In general, any evaluation process has to evaluate the input, the process, the output, and the outcomes. To conclude, the CBME curriculum has been formulated and implemented to produce competent health-care physicians that can improve the health-care outcomes of the community. However, the success of the program has to be determined and there arises the need to periodically evaluate the program. The outcomes of the evaluation can be used to modify the program and thereby ensure better implementation.